(untitled) (Journal of Hama University, 2021)
This research aims to determine the effect of the use of electronic accounting information systems (information system quality, information quality, information system services quality, information system use, information system user satisfaction, and the ultimate benefits of the information system) in managing bank credit risk, in a sample of Syrian private banks. The researchers distributed (100) questionnaires to managers, heads of departments, observers, and members of the administrative cadres responsible for taking different forms and types of decisions based on accounting information in the banks under study. The number of valid questionnaires that were discharged was (82). The researchers analyzed the data using the Statistical Analysis Program (SPSS 25). At the end of this research, the researchers reached a number of conclusions, the most important of which are: There is a significant effect of the use of electronic accounting information systems (information system quality, information quality, information system services quality, information system use, information system user satisfaction, and the ultimate benefits of the information system) in managing bank credit risk in the banks under study.